Enhancing Global Sustainable Higher Education Through Sustainability Window Approach - Gichuru, Eutychus Ngotho (East African Journal of Education Studies, 2024)
The sustainability window approach began as a model that could explain the way to sustainable economic development. This theory places emphasis on ecological, economic and social linkages for making comprehensive analysis and policy towards United Nation’s Sustainable Development Goals. It identifies four theoretically sustainable paths; two associated with economic growth and the others requiring growth conditional or strict adherence to environmental and social criteria. Many studies confirm that higher education institutions have not been able to completely embrace the concept of sustainability window approach. The paper asserts that these are the most effective ways through which global higher education establishments can achieve sustainability: well-being of society, environmental protection, low consumption, and limited social usage. Finally, it concludes by calling on high education institutions to incorporate sustainability window and integrate it with triple bottom line and responsible management education approaches. The paper argues that in order to determine whether such a change might be suitable in different settings, it is recommended that we test this revised framework using empirical evidence